2018
DOI: 10.1016/j.vaccine.2018.04.035
|View full text |Cite
|
Sign up to set email alerts
|

Development of a bivalent conjugate vaccine candidate against malaria transmission and typhoid fever

Abstract: Immune responses to poorly immunogenic antigens, such as polysaccharides, can be enhanced by conjugation to carriers. Our previous studies indicate that conjugation to Vi polysaccharide of Salmonella Typhi may also enhance immunogenicity of some protein carriers. We therefore explored the possibility of generating a bivalent vaccine against Plasmodium falciparum malaria and typhoid fever, which are co-endemic in many parts of the world, by conjugating Vi polysaccharide, an approved antigen in typhoid vaccine, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…Our previous studies exploring the conjugate vaccine platform using Vi conjugated to carrier proteins interestingly showed that some carrier proteins play the dual role as a carrier protein and a protective antigen 28 , 40 , 47 . In this study, we further demonstrated the potential of Vi conjugation to enhance immune responses in mice to carrier protein compared with those induced by the native protein.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous studies exploring the conjugate vaccine platform using Vi conjugated to carrier proteins interestingly showed that some carrier proteins play the dual role as a carrier protein and a protective antigen 28 , 40 , 47 . In this study, we further demonstrated the potential of Vi conjugation to enhance immune responses in mice to carrier protein compared with those induced by the native protein.…”
Section: Discussionmentioning
confidence: 99%
“…Vi-ΔVP8* conjugates were prepared as previously described 28 , 40 . 8 mg of Vi was dissolved in 4 mL of MES buffer (80 mM, pH 4.9), and 250 μL of 50 mg/mL EDAC was added and mixed with agitation for 5 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Functional activity of immune sera was assayed using Standard Membrane Feeding Assay (SMFA) used for determining the transmission blocking activity. 29 A set of Anopheles mosquitos (20–25) were fed on test sera mixed with cultured P. falciparum gametocytes, through a membrane feeding apparatus. After a week delay for development, each mosquito was dissected, and the number of oocysts developed in the midgut was counted.…”
Section: Methodsmentioning
confidence: 99%
“…One strategy to improve the immunogenicity of poorly immunogenic antigens includes presentation in nanoparticles. 2428 We have shown that chemical conjugation of some TBV antigens to carrier proteins (and other macromolecules) generates nanoparticles with enhanced immunogenicity, 2934 and a 22 kDa recombinant protein from domain-1 of Pfs230, conjugated to EPA, is currently being evaluated in clinical trials (clinicaltrial.gov ID: NCT02334462; NCT02942277). Presentation of antigens in a particulate structure or on the particle surface allow them to be more efficiently internalized by antigen-presenting cells (APCs) than soluble antigen.…”
Section: Introductionmentioning
confidence: 99%